Estimacion de los valores de retorno de la altura de ola en la Provincia de Buenos Aires, Argentina - CAVIGLIA, FERNANDO; POUSA, JORGE (Pesquisas em Geociências, 1997)
The wave height recorded at 8 stations along the oceanic coast of the Province of Buenos Aires, Argentina, was analysed to estimate the 50-year return value of wave height at each station. The probability distributions of wave height for the measurements made at Mar de Ajó (1976/85), punta Médanos (northern and southern waveriders, 1981/84), Pinamar (1976/91), Mar del Plata (1968/69), Puerto Quequén (1975/76), Pehuen-Có (1986/88) and El Cóndor (1988) summer resort were tested with the theoretical distributions of Rayleigh, Weibull and Fisher-Tippett I. Excluding Mar de Ajó and El Cóndor, the best fit was obtained with the Fisher-Tippett probability density function. The method of Battjes for estimating the return values of wave height was applied and the resulting 50-year return values were 2.80; 6.90; 7.90; 7.20; 7.21; 8.20; 4.30 and 2.84 m for Mar de Ajó, punta Médanos (northern waverider), punta Médanos (southern waverider), Pinamar, Mar del Plata, Puerto Quequén, Pehuen-Có and El Cóndor, respectively. Lastly, the standard method of extreme values was used to analyse 10 and 16 annual wave height maxima from Mar de Ajó and Pinamar, respectively. The 50-year return values were found to be 2.30 m for Mar de Ajó and 7.20 m for Piramar.